IS DIGITAL HEROIN CREATING DISTURBING BEHAVIORS AMONG CHILDREN? Moderating Role of Smartphone Addicted Parents - Murtaza , Shah Ali; Molnár, Edina (Acta Carolus Robertus, 2021)
Addiction of cell phones, tablets and computers is creating disturbing behaviors among society members universally. The purpose of this study is to describe the influence of digital heroin on youngsters that are students of top Montessori schools and how their parent’s addictive habits acts as a moderator. This research includes the survey of four hundred and fifty respondents, most of them are the parents of children aged between 3 to 8 years in Lahore, Pakistan. Gymboree (a Montessori academy by Beaconhouse), Lahore Grammar School and Choueifat was included in this survey. The results of the survey exhibit that overwhelming usage of digital gadgets has sudden and significant influence on the youngsters’ health; the greater the addiction of parents towards smart phones, greater is the tendency of a child to demonstrate disturbing behavior. Children of this age are having more interaction with digital technology but there is a very fine line between healthy and addictive usage. There are a lot of reasons why parents let their children use smart gadgets for a longer period of time, one of the reasons of which is easy parenting. This research can play a significant role for social science as well as for technological companies who need to realize that the real game lies in long term goodwill and not the short-term profitability through considering the drivers of youngsters’s psychological problem.
Keywords: smart phones; digital heroin; smart phone addiction; disturbing behaviors